Pengembangan Aplikasi “Talkbuddy” Berbasis Android sebagai Media Komunikasi dan Pembelajaran untuk Mahasiswa Tunarungu - Ibnurhus, Gigih Amrillah; Septa, Septa (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to develop the TalkBuddy application, an Android-based platform designed as an inclusive communication and learning medium for deaf students at Pamulang University (Unpam). The application is tailored to meet the needs of deaf students by offering features such as voice-to-text for transcribing conversations, group discussions resembling messaging platforms, access to learning modules, educational videos, the latest education-related news, and a story-sharing space for personal experiences. The research adopts the Research and Development (R&D) method with a data analysis framework encompassing the stages of concept, design, material collection, assembly, testing, and distribution. The trial subjects include two deaf students from Unpam who participated in testing the application to evaluate the effectiveness and practicality of its features. Data were collected through interviews, observations, and questionnaire responses during the trial process. The findings indicate that the TalkBuddy application effectively enhances accessibility and facilitates communication for deaf students. The application's features are deemed relevant and supportive of inclusive learning processes. Moreover, it provides a constructive solution to communication challenges in academic environments. This study is expected to serve as a stepping stone in the development of inclusive technology for higher education.